2012
DOI: 10.1021/ja301926h
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Coadsorption for Carbon Dioxide Capture in Microporous Polymer Sorbents

Abstract: Alcohol-containing polymer networks synthesized by Friedel-Crafts alkylation have surface areas of up to 1015 m(2)/g. Both racemic and chiral microporous binaphthol (BINOL) networks can be produced by a simple, one-step route. The BINOL networks show higher CO(2) capture capacities than their naphthol counterparts under idealized, dry conditions. In the presence of water vapor, however, these BINOL networks adsorb less CO(2) than more hydrophobic analogues, suggesting that idealized measurements may give a poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
197
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(201 citation statements)
references
References 35 publications
2
197
1
1
Order By: Relevance
“…In this context, it is worth noting that along with this heat recovery, we would be substantially reducing the water content of the exhaust gas. In the case of OCC-BECCS, this operation would need to be performed as a matter of course as part of the GPU v processing and the availability of exhaust gas with a lower water content, even if not completely dry, may unlock the utility of other sorbent materials for PCC-BECCS processes which do not normally perform well with high water content gases [22].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is worth noting that along with this heat recovery, we would be substantially reducing the water content of the exhaust gas. In the case of OCC-BECCS, this operation would need to be performed as a matter of course as part of the GPU v processing and the availability of exhaust gas with a lower water content, even if not completely dry, may unlock the utility of other sorbent materials for PCC-BECCS processes which do not normally perform well with high water content gases [22].…”
Section: Discussionmentioning
confidence: 99%
“…Toluene (10 mmol) was added to anhydrous 1,2-dichloroethane (10 mL) under a flow of nitrogen, followed by formaldehyde dimethyl acetal (15,16,17,19,20,23,25,27,30,40, or 50 mmol for 1.5, 1.6, 1.7, 1.9, 2, 2.3, 2.5, 2.7, 3, 4, or 5 equivalents of FDA, respectively). An equimolar amount of iron(III) chloride (15,16,17,19,20,23,25,27,30,40, or 50 mmol) was added and the reaction mixture heated at 80°C for 18 hours. After cooling the solid product was removed by filtration and washed with methanol several times.…”
Section: Methodsmentioning
confidence: 99%
“…23 Benzene derivatives such as toluene, phenol, aniline, binaphthol, tetraphenylmethane, and also aromatic heterocycles have also been used to form HCPs using this facile and cheap approach. [24][25][26][27] HCPs have been used in applications such as gas capture and storage, and heterogeneous catalysis. 28 For example, we have demonstrated that a benzene derived HCP, which possesses excellent stability to strongly acidic conditions, uptakes CO 2 by physical swelling of the porous network.…”
Section: Introductionmentioning
confidence: 99%
“…Various categories of novel materials with extraordinary porosity have been discovered, including silicas (Suhendi et al 2013), zeolites (Wakihara et al 2010), metal-organic frameworks , zeolitic imidazolate frameworks (Cai et al 2014) and carbon materials (Sevilla and Fuertes 2011). With the advantages of outstanding BET surface area and stability, tremendous porous organic polymers (POPs) have been designed (Jiang et al 2009;Dawson et al 2012;Zhao et al 2012;Han et al 2013;Liu et al 2013;Zhu et al 2013;Thompson et al 2014;Zhu and Zhang 2014;Puthiaraj et al 2015). More importantly, the organic skeletons of POPs give rise to their easy-to-functionalize nature so that enhancement of CO 2 /N 2 selectivity is able to be realized via the incorporation of CO 2 -philic groups into networks (Thomas 2010).…”
Section: Introductionmentioning
confidence: 99%